Tong Sampah dari ban bekas (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
This article contains the making of trash cans from used tires. The purpose of this article is toincrease public awareness of the implementation of building materials & environmental hygiene andhow to Utilize used materials in the neighborhood to be used as a garbage bin. This research is doneby direct method of making and questionnaire. From this article can be concluded that the communityto utilize the used materials is still lacking. So, there are still many untapped tires.Keywords: trash bin, community, used tires.